Bmi1 controls tumor development in an Ink4a/Arf-independent manner in a mouse model for glioma - Bruggeman, Sophia W M; Hulsman, Danielle; Tanger, Ellen; Buckle, Tessa; Blom, Marleen; Zevenhoven, John; van Tellingen, Olaf; van Lohuizen, Maarten (Cancer cell, 2007)
The Polycomb group and oncogene Bmi1 is required for the proliferation of various differentiated cells and for the self-renewal of stem cells and leukemic cancer stem cells. Repression of the Ink4a/Arf locus is a well described mechanism through which Bmi1 can exert its proliferative effects. However, we now demonstrate in an orthotopic transplantation model for glioma, a type of cancer harboring cancer stem cells, that Bmi1 is also required for tumor development in an Ink4a/Arf-independent manner. Tumors derived from Bmi1;Ink4a/Arf doubly deficient astrocytes or neural stem cells have a later time of onset and different histological grading. Moreover, in the absence of Ink4a/Arf, Bmi1-deficient cells and tumors display changes in differentiation capacity.